Immunophenotype and metabolism are linked in peripheral blood neutrophils from patients with kidney cancer - A. A. Savchenko; A. G. Borisov; I. V. Kudryavtsev; I. I. Gvozdev; A. V. Moshev (Медицинская иммунология, 2020)
The aim of the present study was to analyze the relationships between expression of activation and adhesion receptors on peripheral blood neutrophils, and intracellular activity of some neutrophil enzymes in patients with kidney cancer (KC). Patients and methods: the KC patients (n = 72) (T3N0M0, clear-cell type) were examined prior to surgical treatment at the Krasnoyarsk Regional Oncology Center. The diagnosis was verified histologically for all KC patients. The phenotype of blood neutrophils was studied using flow cytometry. The surface receptor expression levels of the neutrophils were evaluated by mean fluorescence intensity. NAD and NADP-dependent dehydrogenases activities in purified peripheral blood neutrophils were measured by bioluminescent method. Results: we have found that the phenotypic alterations in circulating KC patients’ neutrophils appeared along with inhibition of main intracellular metabolic processes and were closely linked with them. The features of the phenotypic imbalance in the neutrophils from KC patients were associated with a decrease in blood cells expressing adhesive (CD11b and CD62L) and functional (CD64 and HLA-DR) receptors. Moreover, the patient’s neutrophils expressed CD11b, CD16 and HLA-DR on their cell surface more intensively, than neutrophilic leukocytes from control group. These phenotypic changes in KC patients’ blood neutrophils occurred in parallel with pronounced decrease in immature cells numbers. The metabolic changes of neutrophil cytoplasmic compartment in KC patients were determined by a decrease in Glu6PDH activity (a key and initializing enzyme of the pentose phosphate cycle) and NADH-LDH (anaerobic glycolysis). Mitochondrial metabolism in neutrophils of KC patients was characterized by multidirectional changes in the activity of NAD- and NADP-dependent glutamate dehydrogenases (decreased activity of NAD-dependent and increased activity of NADP-dependent) and a decrease in NADH-MDH activity. The established features in mitochondrial enzymes activities suggest some disturbances of NAD-dependent processes that could lead to down-regulation of aerobic energy processes. We guess that the decreased activity of plastic and energy processes in blood neutrophils of KC patients could affect the receptor expression levels. By means of correlation analysis, we have found that the relationships in KC patients were determined by negative effects of NADHGDH and NADH-LDH activities upon expression of activation and adhesion receptors in blood neutrophils. Of these enzymes, only glutathione reductase activity in neutrophils from KC patients was positively linked with the CD23 and HLA-DR expression. Thus, an increase in activity of energy processes (e.g., coupling the tricarboxylic acid cycle to amino acid metabolism) in blood neutrophils from the patients with kidney cancer could stimulate expression levels of activation and adhesion receptors and potentially increase antitumor activity of neutrophils.